An Unusual Cause of Adult Ileoileal Intussusception - Javid, Mohamed (J Glob Infect Dis, 2020)
Intestinal intussusception in adults is not considered to be common. Clinical presentations may range from an acute presentation to a chronic one and such wide variations make it challenging to establish the diagnosis on time. Adult intussusceptions usually have an identifiable pathological lead point: commonly a polyp, submucosal lipoma, or other tumors. Our patient, a 42-year-old male, presented to us with features of acute intestinal obstruction. He underwent an emergency laparotomy when intussusception of the ileum was noted; the involved bowel segment was resected. Histopathology showed that the lead point was due to tuberculous lesion. Further investigations showed that the patient had pulmonary tuberculosis (TB), which was not identified till then. The patient was started on antituberculous treatment thereafter and the patient recovered well. We intend to present this case to sensitize the readers to the unusual presentation of intestinal TB as intussusception which should be considered especially in countries with high TB endemicity.